2014
DOI: 10.1080/08997659.2014.920735
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Changes in Disease‐Resistant‐Line and Disease‐Susceptible‐Line Juvenile Rainbow Trout Experimentally Infected with Flavobacterium psychrophilum

Abstract: A challenge to selectively breeding fish populations for improved disease resistance in aquaculture is an incomplete understanding of how artificial selection affects innate immunity at the host-pathogen level. The objective of this study was to determine whether Rainbow Trout Oncorhynchus mykiss bred for differential susceptibility to bacterial cold-water disease exhibited altered tissue damage and cellular inflammatory response following experimental challenge with Flavobacterium psychrophilum. Fish from dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…2 cell abundance in the spleen. This observation of similarity in direction of response shared by both genetic lines is in agreement with a hypothesis based on a histopathologic study on the same genetic strains (Marancik et al, 2014b) that differential survival after Fp-challenge results from a divergence of disease magnitude, not altered disease course.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2 cell abundance in the spleen. This observation of similarity in direction of response shared by both genetic lines is in agreement with a hypothesis based on a histopathologic study on the same genetic strains (Marancik et al, 2014b) that differential survival after Fp-challenge results from a divergence of disease magnitude, not altered disease course.…”
Section: Discussionsupporting
confidence: 89%
“…Both genetic lines were generated through a selective breeding program at the National Center for Cool and Cold Water Aquaculture (NCCCWA). A number of innate and acquired immune components reportedly differ between the two lines, with R-line fish having an enhanced capacity for pathogen control relative to the S-line and R-line fish having significantly larger spleens (Marancik et al, 2014b)(Wiens et al, 2013b)(Hadidi et al, 2008), although the latter does not appear to have a protective role (Wiens et al, 2015). Additionally, R-line fish have a higher abundance of Early B-cell Factor-expressing (EBF) cells compared to S-line trout (Zwollo et al, 2015), although the identity of EBF + cells is more complicated than previously assumed (this study).…”
Section: Introductionmentioning
confidence: 99%
“…We report gene expression differences occurring in the spleen, as part of a larger study examining gene expression differences occurring simultaneously within infiltrating peritoneal cavity cells and anterior kidney tissue, as well as, changes in plasma biochemistry and plasma proteins. We chose to initially investigate the spleen as it is a dynamic site of disease manifestation and substantial histological changes occur following Fp injection including an increased inflammatory infiltrate, perisplenitis, splenic necrosis, and increase in average and total splenic ellipsoid area [39]. The degree of perisplenitis and necrosis are higher in ARS-Fp-S line fish compared to ARS-Fp-R line fish, consistent with differential pathogen control [39].…”
Section: Discussionmentioning
confidence: 99%
“…All fish utilized in this study were from the 2014 year class. Single-sire × single-dam matings were made within genetic lines between 3-year-old females and 1-year-old neomales as previously described [39]. Water temperatures in the egg incubation jars were manipulated so that all families hatched within a one-week period [12].…”
Section: Experimental Animals: Generation Of Rainbow Trout Ars-fp-r Amentioning
confidence: 99%
“…Furthermore, Purcell et al (2008) suggested that phenotypic divergence between source stocks and GLB stocks may be related to disease epizootics or other conditions faced by salmonids in the unique environment of the Great Lakes. Differential susceptibility based on genetic differences has been demonstrated by the development of F. psychrophilum-resistant and susceptible strains of RBT (Marancik et al 2014(Marancik et al , 2015.…”
Section: Discussionmentioning
confidence: 99%